2018
DOI: 10.18632/oncotarget.24515
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic cancers: understanding their molecular pathology and the 2016 WHO classification

Abstract: Accumulating evidence suggests that prostatic cancers represent a group of histologically and molecularly heterogeneous diseases with variable clinical courses. In accordance with the increased knowledge of their clinicopathologies and genetics, the World Health Organization (WHO) classification of prostatic cancers has been revised. Additionally, recent data on their comprehensive molecular characterization have increased our understanding of the genomic basis of prostatic cancers and enabled us to classify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 126 publications
0
26
0
1
Order By: Relevance
“…Notably, PCa incidence and associated mortality are nearly two-thirds and over two times higher, respectively, in African-American (AA) men compared to their Caucasian-American (CA) counterparts [ 2 , 3 ]. PCa follows a defined pattern of cellular progression but exhibits diverse molecular pathobiology making it one of most highly heterogeneous cancers [ 4 , 5 ]. The prostate-specific antigen (PSA) test is the primary detection tool for PCa screening.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PCa incidence and associated mortality are nearly two-thirds and over two times higher, respectively, in African-American (AA) men compared to their Caucasian-American (CA) counterparts [ 2 , 3 ]. PCa follows a defined pattern of cellular progression but exhibits diverse molecular pathobiology making it one of most highly heterogeneous cancers [ 4 , 5 ]. The prostate-specific antigen (PSA) test is the primary detection tool for PCa screening.…”
Section: Introductionmentioning
confidence: 99%
“…Gleason grade 5 should be assigned for the sarcomatoid component and glandular element if present should be given grade as per usual rules 17. Tumour marker and immunohistochemical analyses of expressions of PSA, prostatic acid phosphatase, HMW-Ck, TP63 and AMACR are very helpful in reaching the final histopathological diagnosis 18. Recently, an erythroblast transformation–specific gene deletion was detected in sarcomatoid and adenocarcinoma component, confirming that these tumours are derived from the prostate epithelium 19.…”
Section: Discussionmentioning
confidence: 98%
“…Necropsy tissue from both the DKO and HET mice showed that tumors had sarcomatoid pathology. This is a rare, undifferentiated and mesenchymal prostate pathology (<1% of prostate cancer tumors) that is considered to be highly aggressive [25][26][27]. The loss of p53 function may be associated with the development of sarcomatoid tumors in patients.…”
Section: Plos Onementioning
confidence: 99%